Method for producing high-strength hot-dip galvanized steel sheet
By controlling the dew point and atmosphere conditions during the annealing process, the formation of boron nitrides is suppressed, thus solving the surface defect problem caused by coating peeling in high-strength molten galvanized steel sheets and achieving good coating appearance and lightweight vehicle body effect.
Patent Information
- Application Number
- CN202480020168.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2024-03-18
- Publication Date
- 2025-11-04
AI Technical Summary
Existing high-strength molten galvanized steel sheets have gray spot and black spot defects caused by coating peeling, which occur frequently, especially when boron is added, affecting the surface appearance quality.
By controlling the dew point and atmosphere conditions during the annealing process, the formation of boron nitrides can be suppressed. Specific measures include lowering the dew point to form a reducing atmosphere in the temperature range of 300-500℃, heating rapidly in the temperature range of 500℃ to 750℃, shortening the annealing time and optimizing the dew point in the temperature range above 750℃, and adding anti-nitride elements such as antimony in combination with an appropriate Mn to Si content ratio to form Mn-B composite oxides to fix boron.
It effectively suppresses the generation of gray spot and black spot defects, obtains a good coating appearance, and is suitable for structural components such as automotive parts, achieving vehicle body lightweighting and improved fuel efficiency.
Smart Images

Figure BDA0005603213420000261 
Figure BDA0005603213420000271 
Figure BDA0005603213420000281
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a method for manufacturing a high-strength galvannealed steel sheet having a good surface appearance (plating appearance). BACKGROUND
[0002] In order to achieve both reduction in CO2 emission due to weight reduction of a vehicle and improvement in crashworthiness due to high strength of a vehicle body, attempts have been made to make a thin steel sheet for a vehicle high-strength and thin. For example, there are increasing cases in which a high-strength steel sheet having a tensile strength (TS) of 590 MPa or more is applied to a main structural member forming a skeleton of a vehicle cabin in order to increase the strength of the vehicle body.
[0003] As a method for making a steel high-strength, a method of adding quenching elements such as C, Mn, B, Cr, Mo, and the like is generally used. Among them, B has an advantage of being able to achieve a high quenching property improvement effect with a small amount and making a steel high-strength at a low cost, and has a feature of hardly observing formation of inclusions to deteriorate bendability and delayed fracture resistance, and thus is widely used as an added element of a high-strength steel sheet.
[0004] Regarding a high-strength galvannealed steel sheet in which B is added to a base steel sheet, for example, in Patent Literature 1, a technology is disclosed in which, when a base steel sheet having a prescribed composition is subjected to continuous annealing and galvannealing, a temperature region of an annealing furnace at the time of continuous annealing of 750°C or higher is set to a dew point in an atmosphere of -40°C or lower, thereby reducing the oxygen potential at the interface between the steel sheet and the atmosphere, not forming internal oxidation, and suppressing surface enrichment of Si, Mn, and the like, and thus obtaining an excellent plating appearance.
[0005] In addition, in Patent Literature 2, a technology is disclosed in which a ratio of Si enrichment amount to Mn enrichment amount of a surface layer of a base steel sheet is set to 0.7 or more and 1.3 or less, and, at the time of annealing of a cold-rolled steel sheet, the cold-rolled steel sheet heated to a maximum reaching temperature is held in such a manner that the dew point of the atmosphere in the region is -40°C or lower, and thus an excellent plating property is obtained.
[0006] PRIOR ART DOCUMENTS
[0007] PATENT LITERATURE
[0008] Patent Literature 1: Japanese Patent Application Laid-Open No. 2010-255100
[0009] Patent Literature 2: International Publication No. 2020 / 170542 SUMMARY
[0010] PROBLEMS TO BE SOLVED BY THE INVENTION
[0011] However, the inventors of the present application have conducted detailed studies, and as a result, in the molten galvannealed steel sheet obtained in Patent Document 1, another minute surface defect different from the "surface defect caused by reduction in plating layer wettability due to Si, Mn-based oxide generation" that was the object in Patent Document 1, i.e., a defect in which the Si, Mn-based oxide repels the plating layer and generates a region to which the plating layer does not adhere, was observed, and it was found that there was a new problem of suppressing generation of this surface defect. In the production of a molten plated steel sheet, even if the steel sheet does not repel the plating layer, since the adhesion of the steel sheet to the plating layer is weak, there is a phenomenon in which the plating layer that is temporarily adhered to the steel sheet peels off from the steel sheet, and the above surface defect is considered to be a minute defect caused by this phenomenon. In particular, in a steel containing B, it was ascertained that this surface defect caused by plating layer peeling occurred at a high frequency. In addition, in the molten galvannealed steel sheet obtained in Patent Document 2, particularly in a steel containing B, the same surface defect caused by plating layer peeling occurred at a high frequency. The above surface defect is a dot-shaped defect of about 0.1 to 1.0 mm in diameter, and there are defects that appear gray and defects that appear black, which are hereinafter referred to as gray dot defects and black dot defects, respectively.
[0012] The present application was completed in order to solve the newly discovered problem as described above. That is, the object is to provide a production method of a high-strength molten galvannealed steel sheet that is a high-strength molten galvannealed steel sheet in which B is added to a base material steel sheet, and that has a good surface appearance (plating layer appearance) in which generation of gray dot defects and black dot defects on the surface of the plating layer is suppressed.
[0013] Means for solving the problem
[0014] The inventors of the present application have repeatedly conducted intensive studies in order to solve the above problem, and as a result, obtained the following insights.
[0015] (1) The gray dot defect is a concave-shaped defect caused by the plating layer, which although not repelled by the surface of the steel sheet after immersion treatment, is temporarily adhered to the steel sheet, peeling off at the time of contact with a transport roller due to weak adhesion of the plating layer to the steel sheet and adhering to the roller. In addition, the black dot defect is a convex-shaped defect caused by the above plating layer adhering to the roller peeling off from the roller and adhering again to the steel sheet. These surface defects are unique phenomena that occur in the case where the dew point at the time of annealing before plating is low in a base material steel sheet in which B is added, and therefore the problem has not been recognized in the past.
[0016] (2) The investigation and research into the reason why the aforementioned surface defects are unique to the case of adding boron (B) to the base steel sheet and having a low dew point during annealing before plating revealed that B nitrides form on the steel sheet surface only when the dew point is low during annealing. That is, when the dew point is high during annealing, Si and Mn oxides preferentially form on the steel sheet surface, so this phenomenon hardly occurs. Furthermore, if B is not added, the formation of Si and Mn oxides is suppressed when the dew point is low, thus improving the surface appearance quality of the coating. However, when B is added and the dew point is low, although Si and Mn oxides are suppressed, nitrides can exist stably, thus causing defects due to the formation of B nitrides.
[0017] (3) Nitrogen compounds of B are believed to be mainly produced by the following two factors. Consider the countermeasures corresponding to each factor.
[0018] (i) Nitrogen (N) generated from ammonia in the atmosphere is mainly adsorbed or diffused into the steel plate during the heating process, and then reacts with B during the heating or homogenization process in an atmosphere with low oxygen potential. For ammonia, its formation is significantly promoted by the catalytic effect of iron oxide or pure iron obtained by the reduction of iron oxide. Therefore, if the formation of iron oxide is sufficiently suppressed from the initial stage of heating during annealing and the concentration of ammonia in the atmosphere is reduced, the formation of B nitrides can be suppressed.
[0019] (ii) When B does not form oxides under low oxygen potential conditions, B diffuses to the surface of the steel plate in a solid solution state, forming nitrides on the surface. Even under low oxygen potential conditions, if B is fixed as an oxide on the surface or inside the steel plate as a coating that does not easily have an adverse effect on the appearance quality of the coating, the formation of B nitrides can be suppressed.
[0020] (4) In view of the above, it has been found that by controlling the annealing conditions as described below in the annealing process before plating, the formation of B nitrides can be effectively suppressed. As a result, the generation of gray spot defects and black spot defects can be suppressed, and a molten galvanized steel sheet with a good surface appearance (plating appearance) can be obtained.
[0021] (i) In the temperature range of 300–500°C, which has not been controlled in the prior art, a reducing atmosphere of Fe is formed by lowering the dew point, thereby sufficiently suppressing the formation of iron oxide and thus suppressing the amount of ammonia that is a factor in the formation of B nitrides.
[0022] (ii) Furthermore, for the temperature range of 500°C to 750°C where ammonia generation becomes significant and nitrogen begins to adsorb or penetrate into the steel plate, the adsorption or penetration of nitrogen into the steel plate is suppressed by rapidly performing heating.
[0023] (iii) Further, by shortening the annealing time in the temperature region of 750°C or higher and optimizing the dew point to thereby fix a part of B as an oxide, generation of nitride of B due to diffusion of B to the surface of the steel sheet during annealing is suppressed.
[0024] Further, it is also made clear that, in order to suppress adsorption or intrusion of nitrogen to the steel sheet in the temperature region of 500°C or higher and 750°C or lower, addition of Sb is effective; by controlling the ratio of the contents of Mn and Si, i.e., Mn / Si, in a prescribed range, thereby easily generating Mn-B complex oxide, the above-described effect of fixing B as an oxide is obtained; and these aspects contribute to suppression of generation of gray spot defects and black spot defects.
[0025] The present application is completed based on the above insights, and the gist thereof is as follows.
[0026] [1] A method for producing a high-strength galvannealed steel sheet, wherein a steel sheet having the following composition is continuously annealed, immersed in a molten galvanizing bath to perform molten galvanizing, and then, as necessary, subjected to an alloying treatment,
[0027] the composition contains, in mass%,
[0028] C: 0.050% or more and 0.300% or less,
[0029] Si: 1.20% or less,
[0030] Mn: 2.00% or more and 3.50% or less,
[0031] P: 0.100% or less,
[0032] S: 0.0100% or less,
[0033] sol. Al: 1.00% or less,
[0034] N: 0.0200% or less,
[0035] B: 0.0001% or more and 0.0050% or less,
[0036] Sb: 0.001% or more and 0.200% or less, and [ % Mn ] / [ % Si ] is 2.5 or more,
[0037] as necessary, the composition further contains from
[0038] Cr: 1.00% or less,
[0039] Ti: 0.200% or less,
[0040] Nb: 0.200% or less,
[0041] V: 0.200% or less,
[0042] Mo: 2.000% or less,
[0043] Cu: 1.000% or less,
[0044] Ni: 0.500% or less,
[0045] Sn: 0.200% or less,
[0046] Mg: 0.0100% or less,
[0047] Ca: 0.0100% or less,
[0048] Zn: 0.100% or less,
[0049] Co: 0.200% or less,
[0050] Zr: 0.200% or less,
[0051] REM: 0.0100% or less,
[0052] Ta: 0.10% or less,
[0053] Te: 0.10% or less,
[0054] As: 0.10% or less,
[0055] Hf: 0.10% or less,
[0056] Bi: 0.20% or less,
[0057] Pb: 0.20% or less,
[0058] Ge: 0.10% or less,
[0059] Sr: 0.10% or less,
[0060] Cs: 0.10% or less
[0061] one or more selected from the group consisting of
[0062] the balance of the component composition being Fe and unavoidable impurities,
[0063] in the continuous annealing process,
[0064] a steel sheet is heated in a temperature range of 300°C or more and 500°C or less in an atmosphere containing hydrogen: 3 vol% or more and a dew point: -10°C or less, and oxygen: 500 vol ppm or less,
[0065] The temperature region of 500°C or higher and 750°C or lower is set to an atmosphere containing hydrogen: 5 vol% or more and a dew point: -40°C or lower to heat the steel sheet at an average heating rate: 1°C / s or more,
[0066] The temperature of 750°C or higher and 950°C or lower is set to an atmosphere containing hydrogen: 5 vol% or more and a dew point: -55°C or higher and -40°C or lower to perform a soaking treatment of the steel sheet for a holding time: 20 to 300 seconds.
[0067] [2] The method of producing a high-strength galvannealed steel sheet according to the above-mentioned [1], wherein in the component composition of the steel sheet, [%Mn] / [%Si] is 12.0 or more.
[0068] [3] The method of producing a high-strength galvannealed steel sheet according to the above-mentioned [1] or [2], wherein in the process of performing a soaking treatment of the steel sheet at a temperature of 750°C or higher and 950°C or lower in the continuous annealing, an atmosphere of ammonia: 0.010 vol% or less is set.
[0069] Effects of the Invention
[0070] According to the present application, it is possible to produce a high-strength galvannealed steel sheet having a good surface appearance (plating layer appearance) in which generation of a gray spot defect and a black spot defect on a surface of a plated layer is suppressed, by adding B in a base steel sheet. The high-strength galvannealed steel sheet produced by the present application is suitable for structural members such as automobile parts, for example, and fuel efficiency improvement due to a light weight of a vehicle body can be achieved by application to this use. DETAILED DESCRIPTION
[0071] The present application is a high-strength galvannealed steel sheet having a molten galvanized layer on one side or both sides of a steel sheet (base steel sheet), including an alloyed molten galvanized steel sheet in which an alloying treatment is performed after molten galvanizing.
[0072] Here, the composition of the molten galvanized layer is not particularly limited, and can be a general composition. If one example is cited, the molten galvanized layer can have a composition containing Fe: 20 mass% or less, Al: 0.001 mass% or more and 1.0 mass% or less, and further containing 1 or 2 or more kinds selected from Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM, in a total amount of 0 mass% or more and 3.5 mass% or less, with the balance being Zn and unavoidable impurities.
[0073] Generally, in the case of a molten galvanized steel sheet (GI), the Fe content in the plated layer is less than 7 mass%, and in the case of an alloyed molten galvanized steel sheet (GA), the Fe content in the plated layer is 7 mass% or more and 15 mass% or less, and is preferably 8 mass% or more and 13 mass% or less.
[0074] Hereinafter, the composition of the steel sheet (base steel sheet) and the reason for the limitation thereof will be described. Note that in the following description, "%" indicating the content of the component elements of the steel sheet indicates "mass %" unless otherwise specified. In addition, the tensile strength is referred to as TS.
[0075] • C: 0.050% or more and 0.300% or less
[0076] C is an effective element for generating a desired amount of quenched martensite, tempered martensite, and making TS 590 MPa or more and obtaining excellent dimensional accuracy at the time of forming. When the content of C is less than 0.050%, the area ratio of quenched martensite decreases, and in addition, the area ratio of ferrite and bainite increases, making it difficult to make TS 590 MPa or more. On the other hand, if the content of C exceeds 0.300%, the carbon concentration in quenched martensite and tempered martensite increases, and the hardness of quenched martensite and tempered martensite increases. As a result, the hardness difference between ferrite and bainite as soft phases and quenched martensite and tempered martensite as hard phases becomes large, so the blanking property, tensile flange property, and bending property decrease. Therefore, the content of C is set to 0.050% or more and 0.300% or less. In addition, in order to make TS 780 MPa or more, the content of C is preferably set to 0.060% or more, and in order to make TS 980 MPa or more, the content of C is more preferably set to 0.090% or more. In addition, if the content of C is too large, the weldability deteriorates, so the content of C is preferably 0.250% or less, and more preferably 0.220% or less.
[0077] • Si: 1.20% or less
[0078] Si is an effective element for strengthening the steel to obtain good quality, and is also an effective element for improving ductility. On the other hand, if the content of Si exceeds 1.20%, the amount of Si enrichment on the surface of the steel sheet increases at the time of annealing, and Si oxide that becomes a cause of non-plating defects is formed on the surface of the steel sheet, so it is difficult to achieve good plating properties. By making the content of Si 1.20% or less, the generation of Si, Mn-based complex oxides can be suppressed and Mn in the steel sheet can be effectively utilized as Mn, B complex oxides, and gray spot defects and black spot defects can be suppressed. Therefore, the content of Si is set to 1.20% or less. In addition, from the above-mentioned viewpoint, the content of Si is preferably 0.80% or less, and further preferably 0.55% or less.
[0079] The lower limit of the content of Si is not particularly set. That is, the content of Si can also be 0%, but the refining cost increases to reduce to less than 0.01%, and therefore the content of Si is preferably 0.01% or more. Further, from the viewpoint of achieving both high strength and improvement of ductility, the content of Si is preferably 0.05% or more, and further preferably 0.10% or more. Further, particularly from the viewpoint of obtaining high ductility, the content of Si is further preferably 0.15% or more.
[0080] • Mn: 2.00% or more and 3.50% or less
[0081] Mn is an element required to inhibit the occurrence of gray spot defects and black spot defects to obtain good surface quality. By containing 2.00% or more of Mn, Mn-B-based complex oxides which have little adverse effect on the appearance quality of plated layers are formed, and the formation of B nitrides is inhibited, and therefore the occurrence of gray spot defects and black spot defects is inhibited. Further, Mn is also an effective element for generating the required amount of quenched martensite and tempered martensite, and for achieving a TS of 590 MPa or more. When the content of Mn is less than 2.00%, B which forms complex oxides with Mn at the time of annealing decreases, and the amount of BN formed increases, and therefore it is not possible to sufficiently inhibit the occurrence of black spot defects and gray spot defects. On the other hand, when the content of Mn exceeds 3.50%, the area ratio of tempered martensite increases, and the area ratios of ferrite and bainite decrease, and the dimensional accuracy at the time of forming decreases. Further, the amount of Mn which is enriched on the surface of the steel sheet at the time of annealing increases, and Mn oxides which are the cause of non-plating defects are formed in large amounts on the surface of the steel sheet, and therefore it is difficult to achieve good plating properties. Therefore, the content of Mn is set to 2.00% or more and 3.50% or less. Further, from the viewpoint of inhibiting the occurrence of gray spot defects and black spot defects, the content of Mn is preferably 2.30% or more, more preferably 2.50% or more, and further preferably 2.60% or more. Further, from the above viewpoints, the content of Mn is preferably 3.30% or less, and more preferably 3.00% or less.
[0082] • P: 0.100% or less
[0083] P is an element which has the effect of solid solution strengthening and is used to increase the strength of the steel sheet, but when the content of P exceeds 0.100%, P segregates at the grain boundaries of the original austenite and embrittles the grain boundaries, and therefore the blanking properties and the stretch flange properties decrease. Therefore, the content of P is set to 0.100% or less. Further, from the above viewpoints, the content of P is preferably 0.050% or less, and more preferably 0.030% or less.
[0084] The lower limit of the content of P is not set. That is, the content of P can also be 0%, but the refining cost increases when controlled to be less than 0.001%, and therefore the content of P is preferably 0.001% or more.
[0085] • S: 0.0100% or less
[0086] S exists in the steel as a sulfide, and if the content exceeds 0.0100%, the limit deformation capacity of the steel sheet decreases, and thus the punchability, stretch flangeability, and bendability decrease. Therefore, the content of S is set to 0.0100% or less. Note that the lower limit of the content of S is not particularly specified. That is, the content of S can also be 0%, but when controlled to be less than 0.0001%, the refining cost increases, and thus the content of S is preferably 0.0001% or more. In addition, from the above-described viewpoint, the content of S is preferably 0.0050% or less.
[0087] • sol. Al: 1.00% or less
[0088] Al can be used as a deoxidizing material. At this time, the amount of sol. Al in the steel is preferably set to 0.01% or more. In addition, in a steel sheet to which B is added, by adding Al, N in the steel is fixed in the form of AlN, and the added B can be utilized as solid solution B effective for the increase in strength. In addition, Al also has the effect of suppressing the generation of carbides in annealing and increasing the volume fraction of residual austenite. The generated residual austenite has the effect of improving ductility. In order to obtain the effect of fixing N in the form of AlN, sol. Al is preferably contained in an amount of 0.02% or more. In addition, from the viewpoint of obtaining the effect of improving ductility, sol. Al is more preferably contained in an amount of 0.05% or more. However, if the amount of sol. Al exceeds 1.00%, plating does not occur, and thus the amount of sol. Al is set to 1.00% or less. In addition, from the above-described viewpoint, the content of sol. Al is preferably 0.10% or less, and more preferably 0.08% or less.
[0089] • N: 0.0200% or less
[0090] N exists in the steel as a nitride, and if the content exceeds 0.0200%, the limit deformation capacity of the steel sheet decreases, and thus the punchability, stretch flangeability, and bendability decrease. Therefore, the content of N is set to 0.0200% or less. Note that the lower limit of the content of N is not particularly specified, but from the constraint in production technology, the content of N is preferably 0.0005% or more. In addition, from the above-described viewpoint, the content of N is preferably 0.0080% or less.
[0091] The lower limit of the content of N is not set. That is, the content of N can also be 0%, but when controlled to be less than 0.0005%, the refining cost increases, and thus the content of N is preferably 0.0005% or more.
[0092] • B: 0.0001% or more and 0.0050% or less
[0093] B is an element capable of improving the quenching property by segregating at the grain boundaries of austenite. By adding B to the steel, the generation of ferrite and grain growth at the time of annealing cooling can be suppressed. In order to obtain such an effect, it is necessary to make the content of B 0.0001% or more. On the other hand, if the content of B exceeds 0.0050%, a large amount of nitrides are formed on the surface of the steel sheet, and the plating adhesion becomes poor, and appearance defects due to peeling of the plating layer will occur. Therefore, the content of B is set to 0.0001% or more and 0.0050% or less. In addition, from the above viewpoint, the content of B is preferably 0.0002% or more. Also from the above viewpoint, the content of B is preferably 0.0030% or less.
[0094] • Sb: 0.001% or more and 0.200% or less
[0095] Sb is an element known as a nitride suppression element. By adding Sb, the adsorption or penetration of nitrogen into the steel sheet in the temperature range of 500°C or more and 750°C or less is suppressed, and the generation of nitrides of B, which is a factor in the generation of gray spot defects and black spot defects, is suppressed. In order to obtain such an effect, it is necessary to make the content of Sb 0.001% or more. On the other hand, Sb has the effect of grain boundary embrittlement, so if the content of Sb exceeds 0.200%, slab cracks at the time of hot rolling occur. Therefore, the content of Sb is set to 0.001% or more and 0.200% or less. In addition, from the above viewpoint, the content of Sb is preferably 0.005% or more. Also from the above viewpoint, the content of Sb is preferably 0.100% or less.
[0096] • [% Mn] / [% Si]: 2.5 or more
[0097] [%Mn] is the content of Mn, and [%Si] is the content of Si. By making [%Mn] / [%Si] 2.5 or greater, the formation of Si alone oxide is suppressed, non-plating is suppressed, and Mn, B complex oxide is formed in the annealing method of the present application, thereby suppressing the gray spot defect, the black spot defect. Therefore, [%Mn] / [%Si] is set to 2.5 or greater. In addition, from the viewpoint of suppressing the gray spot defect, the black spot defect, [%Mn] / [%Si] is preferably 4.0 or greater, more preferably 6.0 or greater, and further preferably 12.0 or greater. Particularly, by making [%Mn] / [%Si] 12.0 or greater, the formation of Mn, B complex oxide is promoted, and the formation of nitride of B which is a cause of the gray spot defect and the black spot defect is more effectively suppressed. Furthermore, by making [%Mn] / [%Si] 14.0 or greater, the formation of Mn, B complex oxide is particularly remarkably promoted, and also the formation of a slight unevenness which is a precursor of the gray spot defect and the black spot defect is suppressed, and therefore, [%Mn] / [%Si] is more preferably 14.0 or greater. The upper limit is not particularly specified, but in order to suppress the formation of excess Mn, B complex oxide, it is preferably 300.0 or less.
[0098] • Optional addition elements
[0099] The high-strength steel sheet used in the present application can contain, in addition to the above-described composition, one or more selected from Cr: 1.00% or less, Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Mo: 2.000% or less, Cu: 1.000% or less, Ni: 0.500% or less, Sn: 0.200% or less, Mg: 0.0100% or less, Ca: 0.0100% or less, Zn: 0.100% or less, Co: 0.200% or less, Zr: 0.200% or less, REM: 0.0100% or less, Ta: 0.10% or less, Te: 0.10% or less, As: 0.10% or less, Hf: 0.10% or less, Bi: 0.20% or less, Pb: 0.20% or less, Ge: 0.10% or less, Sr: 0.10% or less, Cs: 0.10% or less, in mass%. That is, each of the above-described elements is an optional addition element added as needed, and the effect of the present application can be obtained even if it is 0%, and therefore each of the above-described elements can be 0%.
[0100] Cr is an element that increases the hardenability, and is an effective element for making the TS 590 MPa or more by generating a desired amount of quenched martensite and tempered martensite, and obtaining excellent dimensional accuracy at the time of forming. However, if the content of Cr exceeds 1.00%, the plated layer appearance quality deteriorates, and the area ratio of quenched martensite and tempered martensite increases, the area ratio of ferrite and bainite decreases, and the dimensional accuracy at the time of forming decreases. Therefore, in the case of adding Cr, the content thereof is preferably 1.00% or less. In addition, from the viewpoint of improving the plated layer appearance quality, the content of Cr is more preferably 0.75% or less. In addition, in order to obtain the effect of increasing the hardenability by Cr, the content of Cr is preferably 0.02% or more.
[0101] Ti increases the TS by forming fine carbides, nitrides or carbonitrides at the time of hot rolling or annealing. However, if the content of Ti exceeds 0.200%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of bending test, and thus the bendability decreases. Therefore, in the case of adding Ti, the content thereof is preferably 0.200% or less. In addition, from the above viewpoint, the content of Ti is more preferably 0.100% or less. In addition, in order to obtain the above effect, the content of Ti is preferably 0.005% or more, and more preferably 0.010% or more.
[0102] Nb also increases the TS by forming fine carbides, nitrides or carbonitrides at the time of hot rolling or annealing. However, if the content of Nb exceeds 0.200%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of bending test, and thus the bendability decreases. Therefore, in the case of adding Nb, the content thereof is preferably 0.200% or less. In addition, from the above viewpoint, the content of Nb is more preferably 0.100% or less. In addition, in order to obtain the above effect, the content of Nb is preferably 0.005% or more, and more preferably 0.010% or more.
[0103] V also increases the TS by forming fine carbides, nitrides or carbonitrides at the time of hot rolling or annealing. However, if the content of V exceeds 0.200%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of bending test, and thus the bendability decreases. Therefore, in the case of adding V, the content thereof is preferably 0.200% or less. In addition, from the above viewpoint, the content of V is more preferably 0.100% or less. In addition, in order to obtain the above effect, the content of V is preferably 0.005% or more, and more preferably 0.010% or more.
[0104] Mo is an element that increases quenching property, and is effective for making the area ratio of quenched martensite and tempered martensite be in a more preferable range, further improving TS, and further improving dimensional accuracy at the time of forming. However, if the content of Mo exceeds 2.000%, the area ratio of quenched martensite and tempered martensite increases, it is difficult to make TS be 590 MPa or more, and the dimensional accuracy at the time of forming decreases. In addition, coarse precipitates and inclusions increase, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting point of cracking at the time of bending test, so the bendability decreases. Therefore, in the case where Mo is added, the content thereof is preferably 2.000% or less. In addition, from the above viewpoint, the content of Mo is more preferably 0.500% or less. In addition, in order to obtain the above effects, the content of Mo is preferably 0.005% or more, and more preferably 0.020% or more.
[0105] Cu is an element that increases quenching property, and is effective for making the area ratio of quenched martensite and tempered martensite be in a more preferable range, further improving TS, and further improving dimensional accuracy at the time of forming. However, if the content of Cu exceeds 1.000%, the area ratio of quenched martensite and tempered martensite increases, it is difficult to make TS be 590 MPa or more, and it is difficult to obtain excellent dimensional accuracy at the time of forming. In addition, coarse precipitates and inclusions increase, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting point of cracking at the time of bending test, so the bendability decreases. Therefore, in the case where Cu is added, the content thereof is preferably 1.000% or less. In addition, from the above viewpoint, the content of Cu is more preferably 0.200% or less. In addition, in order to obtain the above effects, the content of Cu is preferably 0.005% or more, and more preferably 0.020% or more.
[0106] Ni is an element that increases quenching property, and is effective for making the area ratio of quenched martensite and tempered martensite be in a more preferable range, further improving TS, and further improving dimensional accuracy at the time of forming. However, if the content of Ni exceeds 0.500%, the area ratio of quenched martensite and tempered martensite increases, TS and the dimensional accuracy at the time of forming decrease. In addition, coarse precipitates and inclusions increase, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting point of cracking at the time of bending test, so the bendability decreases. Therefore, in the case where Ni is added, the content thereof is preferably 0.500% or less. In addition, from the above viewpoint, the content of Ni is more preferably 0.200% or less. In addition, in order to obtain the above effects, the content of Ni is preferably 0.005% or more, and more preferably 0.020% or more.
[0107] Sn is an effective element for suppressing oxidation of the surface of the base steel sheet during annealing and obtaining a more excellent plating property. However, if the content of Sn exceeds 0.200%, coarse precipitates and inclusions increase, and in the case where diffusible hydrogen is contained in the base steel sheet, the precipitates and inclusions become the starting points of cracks at the time of a bending test, and thus the bendability decreases. Therefore, in the case where Sn is added, the content of Sn is preferably 0.200% or less. In addition, from the above viewpoint, the content of Sn is more preferably 0.050% or less. In addition, in order to obtain the above effects, the content of Sn is preferably 0.001% or more, and more preferably 0.005% or more.
[0108] Mg is an effective element for spheroidizing the shape of inclusions such as sulfides and oxides, thereby improving the limit deformation capacity of the steel sheet and improving the stretch flangeability. However, if the content of Mg exceeds 0.0100%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of a bending test, and thus the bendability decreases. Therefore, in the case where Mg is added, the content thereof is preferably 0.0100% or less. In addition, from the above viewpoint, the content of Mg is more preferably 0.0050% or less. In addition, in order to obtain the above effects, the content of Mg is preferably 0.0001% or more, and more preferably 0.0005% or more.
[0109] Ca exists in the base steel sheet in the form of inclusions. If the content of Ca exceeds 0.0100%, in the case where diffusible hydrogen is contained in the base steel sheet, the above inclusions become the starting points of cracks at the time of a bending test, and thus the bendability decreases. Therefore, the content of Ca is preferably 0.0100% or less. Note that the lower limit of the content of Ca can also be 0.0000%, but from the viewpoint of production technology, the content of Ca is preferably 0.0001% or more. In addition, from the above viewpoint, the content of Ca is more preferably 0.0020% or less.
[0110] Zn is an effective element for spheroidizing the shape of inclusions and improving the limit deformation capacity of the steel sheet, thereby improving the stretch flangeability. However, if the content of Zn exceeds 0.100%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of a bending test, and thus the bendability decreases. Therefore, in the case where Zn is added, the content thereof is preferably 0.100% or less. In addition, from the above viewpoint, the content of Zn is more preferably 0.020% or less, and further preferably 0.010% or less. In addition, in order to obtain the above effects, the content of Zn is preferably 0.001% or more, and more preferably 0.002% or more.
[0111] Co is also an effective element for spheroidizing the shape of inclusions and improving the limit deformation capacity of the steel sheet, thereby improving the stretch flangeability. However, if the content of Co exceeds 0.200%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of a bend test, and thus the bendability is reduced. Therefore, in the case where Co is added, the content thereof is preferably 0.200% or less. Further, from the above viewpoint, the content of Co is more preferably 0.010% or less. In addition, in order to obtain the above effects, the content of Co is preferably 0.001% or more, and more preferably 0.005% or more.
[0112] Zr is also an effective element for spheroidizing the shape of inclusions and improving the limit deformation capacity of the steel sheet, thereby improving the stretch flangeability. However, if the content of Zr exceeds 0.200%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of a bend test, and thus the bendability is reduced. Therefore, in the case where Zr is added, the content thereof is preferably 0.200% or less. Further, from the above viewpoint, the content of Zr is more preferably 0.010% or less. In addition, in order to obtain the above effects, the content of Zr is preferably 0.001% or more, and more preferably 0.005% or more.
[0113] REM is also an effective element for spheroidizing the shape of inclusions and improving the limit deformation capacity of the steel sheet, thereby improving the stretch flangeability. However, if the total content of REM exceeds 0.0100%, coarse precipitates and inclusions are generated in large amounts, and in the case where diffusible hydrogen is contained in the steel sheet, the precipitates and inclusions become the starting points of cracks at the time of a bend test, and thus the bendability is reduced. Therefore, in the case where REM is added, the total content thereof is preferably 0.0100% or less. Further, from the above viewpoint, the total content of REM is more preferably 0.0080% or less. In addition, in order to obtain the above effects, the total content of REM is preferably 0.0001% or more, and more preferably 0.0005% or more.
[0114] Ta is an effective element for improving the strength of the base steel sheet, and can be contained as necessary. Ta can be contained in an amount of 0.005% or more to obtain an effect of improving the strength, but from the viewpoint of preventing an increase in cost, the content of Ta is preferably 0.10% or less in the case where Ta is contained.
[0115] Te can control the morphology of sulfides by being contained in an amount of 0.001% or more, thereby improving the ductility and toughness, but from the viewpoint of preventing an increase in cost, the content of Te is preferably 0.10% or less in the case where Te is contained.
[0116] As is contained in an amount of 0.001% or more to control the morphology of sulfides, thereby improving ductility and toughness, but from the viewpoint of preventing cost increase, the As content is preferably 0.10% or less in the case of containing As.
[0117] Hf is contained in an amount of 0.01% or more to control the morphology of sulfides, thereby improving ductility and toughness, but from the viewpoint of preventing cost increase, the Hf content is preferably 0.10% or less in the case of containing Hf.
[0118] Bi is contained in an amount of 0.001% or more to suppress grain boundary segregation, thereby improving ductility and toughness. In addition, Bi has an effect of improving machinability to improve the smoothness of a cut end surface, and has an effect of improving the delayed fracture resistance of a cut surface. In the case of containing Bi, from the viewpoint of preventing cost increase, the Bi content is preferably 0.10% or less.
[0119] Pb is contained in an amount of 0.001% or more to suppress grain boundary segregation, thereby improving ductility and toughness. In addition, Pb has an effect of improving machinability to improve the smoothness of a cut end surface, and has an effect of improving the delayed fracture resistance of a cut surface. In the case of containing Pb, from the viewpoint of preventing cost increase, the Pb content is preferably 0.10% or less.
[0120] Even if Ge is contained in an amount of 0.001% or more, it has no great influence on mechanical properties and surface quality. From the viewpoint of preventing cost increase, in the case of containing Ge, the Ge content is set to 0.10% or less.
[0121] Even if Sr is contained in an amount of 0.001% or more, it has no great influence on mechanical properties and surface quality. From the viewpoint of preventing cost increase, in the case of containing Sr, the Sr content is set to 0.10% or less.
[0122] Even if Cs is contained in an amount of 0.001% or more, it has no great influence on mechanical properties and surface quality. From the viewpoint of preventing cost increase, in the case of containing Cs, the Cs content is set to 0.10% or less.
[0123] The balance other than the above components is Fe and unavoidable impurities.
[0124] Next, the manufacturing conditions of the method of the present application will be described.
[0125] In the manufacturing method of the present application, a steel sheet (cold-rolled steel sheet or hot-rolled steel sheet) having the above components is introduced into a continuous melt galvanizing apparatus, and after continuous annealing in the apparatus, melt galvanizing is performed, and further alloying treatment is performed as necessary, to obtain a melt galvanizing steel sheet.
[0126] Generally, a continuous galvannealing apparatus is configured of an annealing furnace and a molten galvanizing device provided on a downstream side of the annealing furnace, the molten galvanizing device having a molten galvanizing bath and a furnace nose connected to a steel strip outlet side of the annealing furnace and having a front end portion immersed in the molten galvanizing bath. As such a continuous galvannealing apparatus, a general continuous galvanizing line (CGL) configured to continuously perform a series of processes including heating, cooling, molten galvanizing, and alloying treatment of a molten galvanizing plated layer is known. Note that, in the above, the alloying treatment of the molten galvanizing is performed as needed, and can not be performed.
[0127] A steel sheet introduced into the continuous galvannealing apparatus is annealed while passing through the annealing furnace provided with a heating zone, a soaking zone, and a cooling zone in this order. The specific annealing conditions are as follows. Note that the number of times of annealing is not particularly limited, and in the present application, the occurrence of the gray spot defect and the black spot defect is suppressed by one time of annealing, and thus one time (one annealing method) is preferred.
[0128] In terms of the occurrence of the surface defects (the gray spot defect and the black spot defect) that are the problems to be solved by the present application, it is a phenomenon peculiar to a case where B is added to a base steel sheet and the dew point at the time of annealing before plating is low, and the problem has not been recognized in the past. As described above, in order to manufacture a molten galvanizing steel sheet in which the occurrence of such surface defects is suppressed and which has a good surface appearance (plated layer appearance), the present inventors have repeatedly conducted intensive research, and as a result, the following findings have been obtained.
[0129] (1) The reason why the gray spot defect and the black spot defect occur is that, in a case where B is added to a base steel sheet and the dew point at the time of annealing is low, a nitride of B is formed on the surface of the steel sheet, and thus the occurrence of the gray spot defect and the black spot defect can be prevented by suppressing the generation of the nitride of B.
[0130] (2) The nitride of B is generated mainly based on two factors, i.e., (i) nitrogen (N) from ammonia in the atmosphere intrudes or is adsorbed to the steel sheet, and reacts with B under a low oxygen potential condition; and (ii) B diffuses to the surface layer of the steel sheet in a solid solution state and forms a nitride at the surface layer under a condition where B does not form an oxide under a low oxygen potential condition. As for the factor of (i) above, as for the generation of ammonia, it is significantly promoted by the catalytic action of iron oxide and pure iron obtained by reduction of the iron oxide using N2 and H2 in the atmosphere as raw materials in a temperature range of 500°C or higher and 750°C or lower, and in conjunction therewith, the intrusion and adsorption of nitrogen to the steel sheet increase. Therefore, if the generation of iron oxide is suppressed in a temperature range of 500°C or lower, and the amount of ammonia generated is reduced, the generation of the nitride of B can be suppressed. In addition, as for the factor of (ii) above, if B is fixed as an oxide on the surface of the steel sheet or inside the steel sheet without easily causing adverse effects on the appearance quality of the plated layer even under a low oxygen potential condition, the generation of the nitride of B can be suppressed.
[0131] (3) In the continuous annealing process before plating, by performing a series of controls of the annealing conditions as described below, the generation of the nitride of B can be effectively suppressed, and as a result, the generation of the gray spot defects and the black spot defects can be effectively suppressed.
[0132] (i) For a temperature range of 300 to 500°C, which has not been controlled in the prior art, a reducing atmosphere of Fe is formed by lowering the dew point, whereby the generation of iron oxide is sufficiently suppressed, and thus the generation of ammonia, which is a factor of the formation of the nitride of B, is suppressed;
[0133] (ii) Furthermore, for a temperature range of 500°C or higher and 750°C or lower, in which the generation of ammonia becomes significant and nitrogen starts to be adsorbed or intruded to the steel sheet, the nitriding of the steel sheet is suppressed by making the heating rapid, and thus the generation of the nitride of B in a temperature range of 750°C or higher is suppressed;
[0134] (iii) Furthermore, by shortening the annealing time in a temperature range of 750°C or higher (soaking zone) and optimizing the dew point so as to fix a part of B as an oxide, the generation of the nitride due to the diffusion of B to the surface of the steel sheet in the annealing is suppressed.
[0135] Therefore, in the present application, the continuous annealing is performed under a series of conditions that are optimized in order to obtain the effects of (3) above, and the series of annealing conditions that are optimized become an extremely important factor in the present application.
[0136] In the continuous annealing process of the present application, first, a temperature region of 300°C or higher and 500°C or lower is set to an atmosphere containing hydrogen: 3 vol% or more and dew point: -10°C or lower, and oxygen concentration: 500 vol ppm or less to heat the steel sheet. In this temperature region, by being set to a reducing atmosphere of Fe, generation of iron oxide is suppressed, and generation of ammonia, which is a factor of nitride formation of B, is suppressed (particularly, generation of ammonia that becomes significant at a temperature region of 500°C or higher).
[0137] • hydrogen concentration of the atmosphere: 3 vol% or more
[0138] Since hydrogen is a reducing gas, oxidation of the steel sheet surface at the time of annealing can be suppressed. In order to sufficiently obtain the oxidation suppression effect, the hydrogen concentration of the atmosphere is 3 vol% or more, and preferably 5 vol% or more. The upper limit of the hydrogen concentration is not particularly limited, and from the viewpoint of suppressing cost increase, it is preferably 30 vol% or less.
[0139] • dew point of the atmosphere: -10°C or lower
[0140] In the low temperature region of 300 to 500°C, if the dew point exceeds -10°C, oxidation of iron occurs on the steel sheet surface, and generation of ammonia in the temperature region of 500°C or higher is promoted. By making the dew point -10°C or lower, oxidation of Fe on the steel sheet surface can be suppressed. Therefore, the dew point is set to -10°C or lower, and in order to sufficiently obtain the generation suppression effect of iron oxide, it is preferably set to -40°C or lower. The lower limit is not particularly limited, but from the viewpoint of preventing cost increase due to lowering of the dew point, it is preferably -60°C or higher.
[0141] • oxygen concentration of the atmosphere: 500 vol ppm or less
[0142] In order to suppress oxidation of Fe at the time of annealing, the oxygen concentration is made 500 vol ppm or less, and preferably 200 vol ppm or less.
[0143] The balance (95 vol% or less) of the atmosphere gas other than hydrogen, H2O, and oxygen is preferably N2 gas and inevitable impurities, and furthermore, a part of this N2 gas can be replaced with one or more of CO gas, CO2 gas, and Ar gas. At this time, the proportion of this replacement gas in the atmosphere gas is preferably 30 vol% or less. The lower limit is not particularly limited, but from the viewpoint of preventing cost increase due to removal of inevitable impurities, it is preferably 0.01 vol% or more.
[0144] • average heating rate in the temperature region of 300°C to 500°C
[0145] As described above, in the case of ammonia as the nitrogen source of B, its generation is promoted with iron oxide and pure iron obtained by reduction of the iron oxide as catalyst. Therefore, from the viewpoint of suppressing the generation of the gray spot defect and the black spot defect, it is preferable to make the average heating rate 10°C / s or less, sufficiently secure the annealing time in the reduction atmosphere of Fe, and reduce the iron oxide on the surface of the steel sheet. Thus, it is possible to form the Mn, B oxides on the surface of the steel sheet as early as possible in the temperature region of 500°C or higher in the subsequent heating, and it is possible to suppress the exposure of the pure iron layer of the surface layer of the steel sheet in the heating and the soaking. On the other hand, in view of the productivity, the average heating rate is preferably 1°C / s or more. In addition, from the above viewpoint, the more preferable range of the average heating rate is 2°C / s or more and 7°C / s or less.
[0146] In the continuous annealing process, the next temperature region of 500°C or higher and 750°C or lower is set to an atmosphere containing hydrogen: 5% by volume or more and a dew point: -40°C or lower to heat the steel sheet at an average heating rate: 1°C / s or more. This temperature region is a temperature region in which the generation of ammonia becomes significant, nitrogen starts to be adsorbed, and permeates into the steel sheet, and thus the generation of ammonia and the permeation of nitrogen are suppressed, and the generation of the nitride of B in the subsequent soaking process is suppressed.
[0147] • Hydrogen concentration of the atmosphere: 5% by volume or more
[0148] Since hydrogen is a reducing gas, it is possible to suppress the formation of the oxides of Si and Mn at the time of annealing, and prevent the non-plating defects caused by the oxides. In order to sufficiently obtain the effect of suppressing the formation of the oxides, the hydrogen concentration of the atmosphere is set to 5% by volume or more, and preferably 6% by volume or more. The upper limit of the hydrogen concentration is not particularly limited, and from the viewpoint of suppressing the increase in cost, it is preferably 30% by volume or less.
[0149] • Dew point of the atmosphere: -40°C or lower
[0150] When the dew point is higher than -40°C, a large amount of oxides of Si and Mn are formed on the surface of the steel sheet, and the non-plating defects caused by the oxides are generated. In addition, since new oxidation of Fe occurs, the suppression of the generation of ammonia in the heating process of 500°C or higher and the soaking process of 750°C or higher becomes insufficient, and the suppression of the gray spot defect and the black spot defect becomes insufficient. Therefore, the dew point is set to -40°C or lower. In addition, from the viewpoint of suppressing the gray spot defect and the black spot defect, the dew point of the atmosphere is further preferably -42°C or lower. The lower limit is not particularly specified, but from the viewpoint of preventing the increase in cost due to the lowering of the dew point, it is preferably -60°C or higher.
[0151] The balance (95 vol% or less) of the atmosphere gas other than hydrogen, H2O, and oxygen is preferably N2 gas and inevitable impurities, and furthermore, a part of the N2 gas can be replaced with one or more of CO gas, CO2 gas, and Ar gas. At this time, the proportion of the replacement gas in the atmosphere gas is preferably 30 vol% or less. The lower limit is not particularly specified, but from the viewpoint of preventing an increase in cost due to removal of inevitable impurities, it is preferably 0.01 vol% or more.
[0152] • Average heating rate: 1°C / s or more
[0153] The nitriding reaction via ammonia is apt to occur in the temperature range of 500 to 750°C. Therefore, from the viewpoint of suppressing the gray spot defect and the black spot defect, it is necessary to rapidly heat this temperature region. At a heating rate of less than 1°C / sec, the time required to raise the temperature to the prescribed temperature becomes long, the amount of nitrogen that penetrates into the steel sheet increases, and a nitride of B is formed in the subsequent soaking process, thus causing appearance defects due to the gray spot defect and the black spot defect. Therefore, the average heating rate is set to 1°C / s or more, preferably 1.5°C / s or more, and more preferably 5°C / s or more. The upper limit is not particularly specified, but it is preferably 20°C / s or less, which can be achieved in a general annealing furnace.
[0154] In the continuous annealing process, the steel sheet is subjected to soaking treatment at a temperature of 750°C or higher and 950°C or lower in an atmosphere containing hydrogen: 5 vol% or more and having a dew point: -55°C or higher and -40°C or lower, for a holding time: 20 to 300 seconds. In this soaking process, the nitriding reaction of B caused by ammonia and nitrogen that has penetrated into the steel sheet is suppressed, and a part of B is fixed as an oxide on the surface of the steel sheet or inside the steel sheet, thereby suppressing the generation of a nitride caused by the diffusion of B on the surface of the steel sheet in annealing. The amount of the nitride of B is thereby suppressed.
[0155] • Hydrogen concentration of the atmosphere: 5 vol% or more
[0156] Since hydrogen is a reducing gas, the formation of oxides of Si and Mn at the time of annealing can be suppressed, and non-plating defects caused by oxides can be prevented. In order to sufficiently obtain the effect of suppressing the formation of oxides, the hydrogen concentration of the atmosphere is set to 5 vol% or more, and preferably 6 vol% or more. The upper limit of the hydrogen concentration is not particularly limited, but from the viewpoint of suppressing an increase in cost, it is preferably 30 vol% or less.
[0157] • Dew point of the atmosphere: -55°C or higher and -40°C or lower
[0158] When the dew point is higher than -40°C, a large amount of oxides of Si and Mn are formed on the surface of the steel sheet, resulting in non-plating defects caused by the oxides. On the other hand, when the dew point is lower than -55°C, a part of B cannot be sufficiently fixed in the form of oxides to suppress the generation of nitrides caused by the diffusion of B to the surface of the steel sheet during annealing. In addition, the oxygen potential of the annealing atmosphere becomes low and the nitrogen potential becomes high, and thus the formation of nitrides becomes stable, and the formation of nitrides of B on the surface of the steel sheet is promoted. As a result, the generation of gray spot defects and black spot defects cannot be properly suppressed. Therefore, the dew point is set to be -55°C or higher, and preferably -50°C or higher. In addition, the dew point is set to be -40°C or lower, and preferably -45°C or lower.
[0159] • Retention time: 20 seconds or more and 300 seconds or less
[0160] When the retention time is shorter than 20 seconds, the proportion of the generation of austenite during heating in the two-phase region of ferrite and austenite becomes insufficient, and thus the area ratio of ferrite and bainite increases, and it becomes difficult to make the TS 590 MPa or more. On the other hand, if the retention time exceeds 300 seconds, although a part of B is fixed as oxides, a part of the remaining portion of B generates nitrides, and thus the amount of nitrides of B formed on the surface of the steel sheet increases, and the generation of gray spot defects and black spot defects cannot be properly suppressed. Therefore, the retention time is set to be 20 seconds or more, and preferably 30 seconds or more. In addition, the retention time is 300 seconds or less, and preferably 100 seconds or less. Note that the retention time refers to the time during which the steel sheet stays in the above-described atmosphere (passes through the atmosphere) at a temperature of 750°C or more and 950°C or less.
[0161] • Ammonia concentration of the atmosphere
[0162] In the present application, it is preferable to reduce the ammonia concentration in the atmosphere in the soaking treatment step to 0.010% by volume or less. As a reason for the inclusion of ammonia in the atmosphere in the soaking zone, there are cases where ammonia gas generated in the heating zone is carried into the soaking zone, cases where exhaust gas mixed with ammonia is reused in the soaking zone to mix ammonia, and the like. In order to alleviate the disadvantages of such inclusion and generation of ammonia, it is important to improve the sealing property of the partition wall between the heating zone and the soaking zone, to reduce the reuse rate of exhaust gas, and to increase the flow rate of new high-purity gas from the rear direction to the front direction of the steel sheet travel direction (from the outlet side to the inlet side of the soaking zone). By reducing the ammonia concentration in the soaking zone, the formation of nitrides of B is further suppressed, and thus appearance defects caused by gray spot defects and black spot defects can be further suppressed. Therefore, it is preferable to set the ammonia concentration in the atmosphere to 0.010% by volume or less. The lower limit is not particularly specified, and from the viewpoint of preventing an increase in cost due to the removal of ammonia, it is preferable to be 0.0001% by volume or more.
[0163] In the present application, after the steel sheet subjected to the continuous annealing under the above conditions is cooled, it is immersed in a molten galvanizing bath to perform a molten galvanizing treatment. The temperature of the above cooling is set to 200 to 520°C, and after heating as necessary, the steel sheet is immersed in the molten galvanizing bath. The bath temperature of the molten galvanizing bath is generally about 440 to 500°C. The molten galvanizing bath is not particularly limited, and for example, a molten galvanizing bath having the following composition can be used: the Al content is 0.10 mass% or more and 0.23 mass% or less, and further, 1 kind or two or more kinds selected from Pb, Sb, Si, Sn, Mg, Mn, Ni, Cr, Co, Ca, Cu, Li, Ti, Be, Bi, and REM are contained in a total amount of 0 mass% or more and 3.5 mass% or less, and the balance is Zn and unavoidable impurities. In addition, in order to prevent the bath temperature of the plating bath from changing, the temperature of the steel sheet before the plating treatment (immersion sheet temperature) is preferably the bath temperature or more and the bath temperature + 50°C or less.
[0164] After the above molten galvanizing treatment, an alloying treatment of the zinc plated layer can also be further performed to form an alloyed molten galvanizing layer. The alloying treatment is preferably performed in a temperature range of 480°C or higher and 570°C or lower. When the alloying temperature is lower than 480°C, the Zn-Fe alloying speed becomes excessively slow, and alloying becomes significantly difficult. On the other hand, when the alloying temperature exceeds 570°C, the untransformed austenite phase is transformed into pearlite, and the TS and the El sometimes decrease. The alloying treatment is more preferably performed in a temperature range of 490°C or higher and 560°C or lower, and further preferably in a temperature range of 490°C or higher and 530°C or lower.
[0165] The plated layer adhesion amount of the molten galvanizing steel sheet (GI) and the alloyed molten galvanizing steel sheet (GA) is preferably 20 to 80 g / m 2 The plated layer adhesion amount can be adjusted by performing gas wiping or the like after the molten galvanizing.
[0166] After the galvannealing treatment, the molten galvanizing steel sheet is cooled to a temperature of 350°C or lower. The cooling rate is not particularly limited, but from the viewpoint of improving the TS and the ductility, the cooling rate from the molten galvanizing to 350°C is preferably 3°C / s or higher and 20°C / s or lower. The cooling rate from the molten galvanizing to room temperature is not particularly limited, but from the viewpoint of further improving the TS, the average cooling rate from the molvanizing to 50°C is preferably 5°C / s or higher. On the other hand, from the viewpoint of the production technology, the average cooling rate from the molvanizing to 50°C is preferably 40°C / s or lower. Further, the average cooling rate from the molvanizing to 50°C is more preferably 7°C / s or higher and 30°C / s or lower. The cooling rate below 50°C is not particularly limited, and the molten galvanizing steel sheet can be cooled to a predetermined temperature by any method.
[0167] As the cooling method after the molten galvanizing or the galvannealing treatment, gas jet cooling, spray cooling, water cooling, air cooling, or the like can be appropriately applied. Note that generally, the high-strength molten galvanizing steel sheet is traded after being cooled to room temperature.
[0168] The molten galvanizing steel sheet cooled to a temperature of 350°C or lower after the molten galvanizing or the galvannealing treatment can be subjected to rolling at a predetermined elongation. The elongation of the rolling is preferably 0.05% or higher and 1.00% or lower. By setting the elongation of the rolling to 0.05% or higher, a crack can be introduced into the zinc plated layer. By introducing a crack into the zinc plated layer, the amount of diffusible hydrogen in the steel sheet can be reduced, and as a result, the bendability and the hole expandability can be improved. On the other hand, if the elongation of the rolling exceeds 1.00%, the YS increases, and the dimensional accuracy at the time of forming decreases. The elongation of the rolling is more preferably 0.70% or lower and 0.10% or higher.
[0169] The rolling described above can be performed on-line in a device connected to the continuous molten galvanizing equipment, or off-line from the continuous molten galvanizing equipment. In addition, the target elongation (for example, 0.05% or higher and 1.00% or lower) can be achieved by one rolling, or the target elongation can be achieved by a plurality of rollings.
[0170] Note that as the rolling described above, a quenching and tempering rolling is generally performed, but as long as the same elongation as that of the quenching and tempering rolling can be imparted, a rolling using a leveler or the like can be performed.
[0171] After the galvannealing or after cooling to 3500C or less, and as necessary after the above-described rolling, the steel sheet can also be held at room temperature or at a temperature region exceeding room temperature and 4500C or less. By holding at room temperature or at a temperature region exceeding room temperature and 4500C or less, the amount of diffusible hydrogen in the steel sheet can be reduced, and the bendability and the hole expandability can be improved. In addition, from the viewpoint of improving the ductility, in the case of cooling to a temperature range of 1500C or more and 3500C or less as described above, it is preferable to heat as necessary after the cooling, and to hold (soak) at a temperature range of 3000C or more and 4500C or less. Here, the holding time at room temperature is usually about 3 days to 10 months, and the soaking time under conditions exceeding room temperature is usually about 1 min to 14 days.
[0172] Note that manufacturing conditions other than the above-described conditions can be used by conventional methods.
[0173] The high-strength galvannealed steel sheet manufactured in the present application can have a TS of 590 MPa or more. In the case of further high-strength, the TS can be 780 MPa or more, or even 980 MPa or more. Note that the TS is measured according to JIS Z2241 as follows. A JIS No. 5 test piece is taken from the galvannealed steel sheet in a manner such that the length direction is perpendicular to the rolling direction of the steel sheet. Using this test piece, a tensile test is performed under conditions in which the crosshead displacement speed Vc is 1.67 x 10 -1 mm / s, and the TS is measured.
[0174] In addition, the thickness of the galvannealed steel sheet manufactured in the present application is not particularly limited, and is usually about 0.3 mm or more and 2.8 mm or less.
[0175] Example
[0176] [Example 1]
[0177] A steel raw material having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) was melted in a converter, and continuously cast to produce a steel billet. The steel billet was heated to 12500C and rough-rolled, and then finish-rolled at a finish-rolling temperature of 9000C and coiled at a coiling temperature of 400 to 6000C to produce a hot-rolled steel sheet. The hot-rolled steel sheet was subjected to pickling treatment, and then cold-rolled to produce a cold-rolled steel sheet having a thickness of 1.4 mm.
[0178] The cold-rolled steel sheet was annealed in a CGL under the conditions shown in Tables 2 to 5, followed by galvannealing under the conditions shown in Tables 2 to 5, and further alloying treatment was performed for a part of the steel sheet after the galvannealing, and cooled to 50°C or lower. Then, temper-rolling was performed at an elongation of 0.1%, and high-strength galvanized steel sheets (GI) and high-strength galvannealed steel sheets (GA) were obtained. Note that, for those not subjected to the alloying treatment, the alloying treatment column in Tables 2 to 4 is indicated as "-".
[0179] As the molten zinc plating bath, in the case of manufacturing GI, a molten zinc plating bath containing Al: 0.20 mass%, the balance being Zn and inevitable impurities was used. In the case of manufacturing GA, a molten zinc plating bath containing Al: 0.14 mass%, the balance being Zn and inevitable impurities was used. In terms of plating layer adhesion amount, in the case of manufacturing GI, 45 to 72 g / m 2 (both sides) or so, and in the case of manufacturing GA, 45 to 55 g / m 2 (both sides) or so.
[0180] In addition, the composition of the plating layer of GI contains Fe: 0.1 to 1.0 mass%, Al: 0.2 to 1.0 mass%, the balance being Fe and inevitable impurities. In addition, the composition of the plating layer of GA contains Fe: 7 to 15 mass%, Al: 0.1 to 1.0 mass%, the balance being Fe and inevitable impurities.
[0181] For the high-strength galvanized steel sheet and the high-strength galvannealed steel sheet obtained as above, the tensile properties and the plating layer appearance were evaluated as follows. The results thereof are shown in Tables 2 to 5 together with the manufacturing conditions.
[0182] • Tensile strength
[0183] The tensile test was performed in accordance with JIS Z2241. From the obtained steel sheet, JIS No. 5 test pieces were collected in a manner that the length direction was perpendicular to the rolling direction of the steel sheet. Using the test pieces, the tensile test was performed under the conditions that the cross head displacement speed Vc: 1.67 x 10 -1 mm / s, and TS was measured.
[0184] • Plating layer appearance
[0185] The appearance of the plated steel sheet was visually observed to check for the presence of ash point defects and black point defects. The front and back surfaces of steel sheets in an area of 1000 mm in the width direction of the coil x 1000 mm in the length direction of the coil were observed, and the observation was performed on N = 5 sheets. In the observed area, a case where no defects were confirmed was rated 3 points, a case where only a minute ash point defect or black point defect of 0.2 mm or less was confirmed was rated 2 points, a case where an ash point defect or black point defect of more than 0.2 mm was confirmed was rated 1 point, and a case where plating was not confirmed as having existed in the past was rated 0 point, and the higher the score of the steel sheet, the better the appearance of the plated layer, and a score of 2 points or more was judged to be acceptable. In addition, in a case where no ash point defects or black point defects were observed, a case where a particularly beautiful surface condition in which a minute plating unevenness that was a forerunner of these defects was not observed was rated 3+ points.
[0186] As shown in Tables 2 to 5, the plated layer appearance of the molten galvanizing steel sheets of the inventive examples was all good. In addition, a high strength of TS: 590 MPa or more was also achieved, and a molten galvanizing steel sheet that could have both high strength and excellent plating quality was obtained. On the other hand, in the molten galvanizing steel sheets of the comparative examples, appearance defects caused by ash point defects and black point defects were confirmed.
[0187] [Table 1]
[0188]
[0189] [Table 2]
[0190]
[0191] [Table 3]
[0192]
[0193] [Table 4]
[0194]
[0195] [Table 5]
[0196]
[0197] [Example 2]
[0198] From the viewpoint of further reducing the ammonia concentration in the atmosphere of the soaking treatment step (soaking zone), a molten galvanized steel sheet was produced under conditions in which the flow rate of the high-purity gas in the soaking zone was increased. Steel raw materials of Steels A, C, G, I, S, and T of Table 1 were used to produce molten galvanized steel sheets in accordance with the production conditions (hot rolling, cold rolling, continuous annealing, molten galvanizing, alloying treatment, and temper rolling) of Example 1. The tensile properties and the plated layer appearance of the resulting molten galvanized steel sheets were evaluated in the same manner as in Example 1. The results thereof are shown in Table 6 together with the production conditions.
[0199] The concentration of ammonia gas was measured at the upper portion of the furnace in the central portion of the long side direction of the production line including the soaking zone of the CGL. The measurement method used ion chromatography.
[0200] As shown in Table 6, by reducing the ammonia concentration in the soaking treatment step (soaking zone) to 0.010 vol% or less, the surface quality (plated layer appearance) of the molten galvanized steel sheet was further improved.
[0201] [Table 6]
[0202]
Claims
1. A method for manufacturing high-strength galvanized steel sheet, wherein, After continuous annealing, the steel sheet with the following composition is immersed in a molten zinc bath for molten zinc plating, and then alloyed as needed. The composition of the ingredients contains, by mass%, C: 0.050% to 0.300% Si: below 1.20% Mn: 2.00% to 3.50% P: below 0.100% S: below 0.0100% sol.Al: 1.00% or less, N: below 0.0200% B: 0.0001% to 0.0050% Sb: ≥0.001% ≤ 0.200%, and [%Mn] / [%Si] ≥2.5 As needed, the composition may further contain ingredients from Cr: less than 1.00% Ti: below 0.200% Nb: below 0.200% V: Below 0.200% Mo: 2.000% or less, Cu: less than 1.000% Ni: below 0.500% Sn: below 0.200% Mg: less than 0.0100% Ca: below 0.0100% Zn: below 0.100% Co: less than 0.200% Zr: below 0.200% REM: below 0.0100% Ta: below 0.10% Te: less than 0.10% As: less than 0.10% Hf: below 0.10% Bi: below 0.20% Pb: below 0.20% Ge: below 0.10% Sr: below 0.10% Cs: below 0.10% Choose one or more from the options. The balance in the composition is Fe and unavoidable impurities. In the continuous annealing process. The steel plate was heated in an atmosphere containing hydrogen (more than 3% by volume), with a dew point below -10°C, and oxygen (less than 500 ppm by volume) within a temperature range of 300°C to 500°C. The steel plate is heated at an average heating rate of 1°C / s or higher in an atmosphere containing hydrogen of 5% by volume or higher and with a dew point of -40°C or lower, within a temperature range of 500°C to 750°C. The steel plate is subjected to homogenization treatment at a temperature of 750°C to 950°C, in an atmosphere containing hydrogen of 5% by volume or more and with a dew point of -55°C to -40°C, for a duration of 20 to 300 seconds.
2. The method for manufacturing high-strength fused galvanized steel sheet according to claim 1, wherein, In the composition of the steel plate, the ratio of [%Mn] to [%Si] is 12.0 or higher.
3. The method for manufacturing high-strength galvanized steel sheet according to claim 1 or 2, wherein, In the continuous annealing process, during the homogenization treatment of steel plates at temperatures above 750°C and below 950°C, the atmosphere is set to ammonia: 0.010% by volume or less.
Citation Information
Patent Citations
High-strength hot-dip galvanized steel plate and method for producing the same
JP2010255100A
High-strength hot-dip galvanized steel sheet and method for manufacturing same
WO2020170542A1